Integrating transcriptomic and metabolomic analysis in roots of wild soybean seedlings in response to low-phosphorus stress - Li, Mingxia; Zhou, Ji; Lang, Xianyu; Han, Defu; Hu, Yongjun; Ding, Yinan; Wang, Guangye; Guo, Jixun; Shi, Lianxuan (Frontiers in Plant Science, 2022)
Plants undergo divergent adaptations to form different ecotypes when exposed to different habitats. Ecotypes with ecological adaptation advantages are excellent germplasm resources for crop improvement. This study comprehensively compared the differences in morphology and physiological mechanisms in the roots of two different ecotypes of wild soybean (Glycine soja) seedlings under artificially simulated low-phosphorus stress. The seedlings of barren-tolerant wild soybean (GS2) suffered less damage than common wild soybean (GS1), and GS2 absorbed more phosphorus by increasing root length. In-depth integrated analyses of transcriptomics and metabolomics revealed the formation process of the ecological adaptability of the two different ecotypes of wild soybean from the perspective of gene expression and metabolic changes. The results showed that the metabolism of phenolic compounds, lignin, and organic acid metabolism was enhanced. Genes encoding pectinesterase and phospholipase C (PLC) were specifically up-regulated, and genes encoding SQD2 (the key enzyme of sulfolipid substitution of phospholipids) were significantly up-regulated in GS2 seedling roots. The key metabolites, putrescine and ascorbate, and the genes encoding the key enzymes L-ascorbate peroxidase and glutathione peroxidase were significantly up-regulated in the ascorbate–glutathione cycle. Wild soybean can resist soil phosphorus deficiency by activating unavailable soil phosphorus, reusing plant structural phosphorus, rebuilding membrane lipids, and enhancing the antioxidant membrane protection system. This study reveals the adaptation process of barren-tolerant wild soybean to poor soil from the perspective of the adaptation of structural and molecular metabolism, and provides a new perspective for the study of divergent adaptation of plants.